2015
DOI: 10.1186/s13072-015-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-faceted quantitative proteomics analysis of histone H2B isoforms and their modifications

Abstract: BackgroundHistone isoforms and their post-translational modifications (PTMs) play an important role in the control of many chromatin-related processes including transcription and DNA damage. Variants of histones H2A and H3 have been studied in depth and have been found to have distinct functions. Although 13 somatic histone H2B isoforms have been identified by various biochemical and mass spectrometric (MS) approaches, the distinct roles of these isoforms within human cells are as yet unknown. Here, we have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 50 publications
2
51
0
1
Order By: Relevance
“…Underscoring that importance, the expression of H2B histone variants is cell-type specific, differentiation stage-dependent as well as cancer-stage and type dependent (38). However, the study of these variants has remained difficult largely because they differ by very few amino acids (Table I; supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Underscoring that importance, the expression of H2B histone variants is cell-type specific, differentiation stage-dependent as well as cancer-stage and type dependent (38). However, the study of these variants has remained difficult largely because they differ by very few amino acids (Table I; supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S1), making variant-specific antibodies virtually impossible to develop. However, the use of top-down MS/MS has proven to be an invaluable tool to study such closely related histone variants (38). This type of mass spectrometry characterizes the histone proteome in an unbiased approach, providing a sequence that does not rely on the existence of modification-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we showed that histone H2B variants were abnormally expressed following iAs exposure, and during the subsequent iAs-mediated epithelial-mesenchymal transition (EMT) (73). We identified a total of 16 H2B variants, 13 somatic and three testis-specific; of the somatic variants, seven were upregulated while three were downregulated (73)(74)(75)(76)(77). The most significant changes observed in our study were the upregulation of histones H2B1K and H2B1C, and downregulation of histones H2B1D and H2B1B.…”
Section: Histone Variantsmentioning
confidence: 69%